1996
DOI: 10.2144/96205bm12
|View full text |Cite
|
Sign up to set email alerts
|

Reducing “Double Sequences” in Automated DNA Sequencing with T7 DNA Polymerase and Internal Labeling

Abstract: improved method for the isolation of highly polymerized native deoxyribonucleic acid from certain protozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…5 and 6). Performing sequencing reactions at high temperatures (cycle sequencing with thermostable polymerases such as Taq, Tth, or SequiTherm, or non-cycling sequencing using IsoTherm) and adding detergents such as Triton X-100 [18], or organic solvents such as DMSO [14,28], can correct such compressions when using dye-primers. The use of dyelabeled dideoxynucleotide terminators also virtually eliminates this problem.…”
Section: Four-color Dna Sequencingmentioning
confidence: 99%
“…5 and 6). Performing sequencing reactions at high temperatures (cycle sequencing with thermostable polymerases such as Taq, Tth, or SequiTherm, or non-cycling sequencing using IsoTherm) and adding detergents such as Triton X-100 [18], or organic solvents such as DMSO [14,28], can correct such compressions when using dye-primers. The use of dyelabeled dideoxynucleotide terminators also virtually eliminates this problem.…”
Section: Four-color Dna Sequencingmentioning
confidence: 99%
“…The detection was chemiluminescent using CSPD (Boehringer) ~G Gz~ Gc~ TAG CaG AGA GGA GGA GGA AGT TTC TGA AGr CAC TGA TAT Z~ GGA for Southern blots, or colorimetric using the NBT/BCIP protocol (B ) [19] hyb GTT ACT GTT GCA ACT GGA TTr CCA AAG TCA CTA TTA ATA GAT TCC TCA GGA AAT CCG GTA USA) following the protocol described in [21]. Electrophoresis and z23 z3z ~4~…”
mentioning
confidence: 99%
“…The use of fluorescein dATP further boosted the read length obtained . The variation in the quality of the sequence noted during routine use (Hawkins et al, 1992) was clarified somewhat after the detailed demands made on the primer and the target sequences were revealed and refined (Wiemann et al, 1996). A screening of the polymerases, which had in the meantime become a target for genetic manipulation (Tabor and Richardson, 1995) showed that by no means all enzymes routinely used in sequencing would accept fluorescent dNTPs as substrates (Voss et al, 1997).…”
Section: B Labelling the Growing Dna Chain (Fig 1b)mentioning
confidence: 99%